'The dream of social flying': social class, higher education choice and the paradox of widening participation - Byrom, Tina (2008)
Widening Participation in UK universities is currently a key political concern. Whilst the under-representation of particular groups has been a feature of higher education for many years, participation for groups identified by gender, ethnicity and disability has seen some improvement. However, the participation of students from low social class groups remains an issue.